2016
DOI: 10.1179/2050854915y.0000000011
|View full text |Cite
|
Sign up to set email alerts
|

Does Levonorgestrel Emergency Contraceptive have a Post-Fertilization Effect? A Review of its Mechanism of Action

Abstract: Background: Recent studies have identified that levonorgestrel administered orally in emergency contraception (LNG-EC) is only efficacious when taken before ovulation. However, the drug does not consistently prevent follicular rupture or impair sperm function. Objective: The present systematic review is performed to analyze and more precisely define the extent to which pre-fertilization mechanisms of action may explain the drug's efficacy in pregnancy avoidance. We also examine the available evidence to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…It can prevent or delay ovulation, increase the thickness of the cervical mucus, and disrupt the corpus luteum formation (12). Recent studies showed that preovulatory levonorgestrel administration can lead to post-fertilization luteal effects and may explain its clinical effects when used before ovulation (13). In a follow-up study, children exposed to levonorgestrel were compared with a control group of children over a period of 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…It can prevent or delay ovulation, increase the thickness of the cervical mucus, and disrupt the corpus luteum formation (12). Recent studies showed that preovulatory levonorgestrel administration can lead to post-fertilization luteal effects and may explain its clinical effects when used before ovulation (13). In a follow-up study, children exposed to levonorgestrel were compared with a control group of children over a period of 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…UPA on the other hand, has a decreasing effect as ovulation approaches but, since it blocks progesterone receptors, prevents implantation ( Mozzanega et al, 2014 ). Mozzanega and Nardelli (2019) consider the mechanisms of LNG and UPA from the viewpoint of informed consent since there is significant ethical concern if the action is directed toward the conceptus ( Kahlenborn et al, 2015 ; Peck et al, 2016 ).…”
Section: Glycodelinmentioning
confidence: 99%
“…In those days, in which most fertilizations do occur [1][2][3]12 , ECPs transform the endometrium into an inhospitable environment for the embryo. As to Levonorgestrel (LNG;Norlevo ® ,Levonelle ® ,Escapelle ® ), we showed that it does never affect ovulation [16][17][18] . Besides, we highlighted that the FIGO (International Federation of Gynecology & Obstetrics) and ICEC (International Consortium for Emergency Contraception) share a false information in their 2008, 2011 and 2012 joint Statements 15 : in fact, they state as a dogma that LNG-ECPs delay or inhibit ovulation and consequently prevent fertilization, without ever affecting embryoimplantation, while -on the contrary -in the studies quoted in support 15,[19][20][21][22][23] ovulation is never inhibited when LNG is taken in the most fertile days of the cycle.…”
Section: Introductionmentioning
confidence: 97%